2016
DOI: 10.1038/srep31491
|View full text |Cite
|
Sign up to set email alerts
|

Urothelium muscarinic activation phosphorylates CBSSer227 via cGMP/PKG pathway causing human bladder relaxation through H2S production

Abstract: The urothelium modulates detrusor activity through releasing factors whose nature has not been clearly defined. Here we have investigated the involvement of H2S as possible mediator released downstream following muscarinic (M) activation, by using human bladder and urothelial T24 cell line. Carbachol stimulation enhances H2S production and in turn cGMP in human urothelium or in T24 cells. This effect is reversed by cysthationine-β-synthase (CBS) inhibition. The blockade of M1 and M3 receptors reverses the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 41 publications
1
32
0
2
Order By: Relevance
“…In this study, both enzymes were undetectable at the gene or protein level in the bladder of Wistar rats. Even though gene expression levels of both enzymes in the bladder have not been investigated before, some reports showed that protein bands of CBS and CSE were detected in the bladder of humans and Sprague‐Dawley rats and CBS protein bands were detected in a human urothelial cell line (T24 cells) . Immunoreactivity of both enzymes was observed in nerve fibers in the smooth muscle layer of the pig bladder neck, while in the human bladder, mainly CSE was detected in the smooth muscle layer, but not in the urothelium .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, both enzymes were undetectable at the gene or protein level in the bladder of Wistar rats. Even though gene expression levels of both enzymes in the bladder have not been investigated before, some reports showed that protein bands of CBS and CSE were detected in the bladder of humans and Sprague‐Dawley rats and CBS protein bands were detected in a human urothelial cell line (T24 cells) . Immunoreactivity of both enzymes was observed in nerve fibers in the smooth muscle layer of the pig bladder neck, while in the human bladder, mainly CSE was detected in the smooth muscle layer, but not in the urothelium .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in this study, rat BL‐D and BL‐T strips contained these components and enzymes related to H 2 S biosynthesis were expressed not only in the smooth muscle layer but also in the urothelium of both bladder tissues. In addition, human urothelium samples treated with L‐cysteine generated H 2 S in vitro . Therefore, the response of H 2 S to a detrusor might differ with or without an urothelium, which can regulate detrusor smooth muscle contractility as a source of endogenous H 2 S. Even though it is unclear whether there are any species‐specific differences in the response of H 2 S in the bladder among Wistar rats, Sprague‐Dawley rats, guinea pigs, and humans, exogenous H 2 S can induce relaxation of the Wistar rat bladder and prostate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is well established that cystine and glutamate are substrates of system xc - , it has been recently demonstrated that cystathionine is a novel substrate of the cystine/glutamate transporter [39]. Cystathionine-β-synthase (CBS), a key enzyme in the trans-sulfuration metabolic pathway involved in the modulation of H 2 S production [40,41], converts homocysteine to cystathionine, which is converted by CSE to cysteine required for synthesis of the antioxidant glutathione GSH [37]. Silencing CBS severely reduces cellular GSH levels [42].…”
Section: Discussionmentioning
confidence: 99%